Sozophytes of steppe zone of Ukraine and their representativeness in the projected econet (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The work is implemented on the analysis basis of rare biodiversity of the region, which is the most vulnerable, is extraordinary fragmented and distinguished by the considerable degradation of ecosystems, capacity of which is mainly exhausted. An analysis of systematic, ecological and geographical structures of sozophytes of Ukraine steppe zone and econet components was realized. It is established that at the territory of projected econet contains 173 species of vascular plants listed in the Red Data Book of Ukraine (RDBU) (2009), i.e. 73,6 % of their number in steppe zone. A comparative analysis of flora of ten leading families of rare species in Ukrainian steppe zone and in the econet components was not found considerable differentiations by its indicators. It is identified that the species of Fabaceae, Poaceae and Orchidaceae families occupy the main places. It is showed that the projected econet mainly represents all conditions to conserve, restore and protect species listed in the RDBU. The found distribution of rare specific composition at territories of administrative regions it could be taken for the reference point to estimate the effectiveness of inclusion of geosystems suitable for their conservation and to develop restoration and protection measures, in particular in the places of the projected econet. Species listed in the RDBU in components of the projected econet of administrative territories occur very unevenly and, of course, is distinguished from the natural. By the likeness Jaccar coefficient between rare flora of the territory of administrative regions and marked in the econet components of steppe Ukraine zone it is defined that Kherson (0,9), Mykolaiv and Donetsk (0,7), Odessa (0,56) regions are the most similar. The rare species of steppe Ukraine zone are insufficiently represented. It is stipulated for the degree of flora and its rare components study. The coefficient of likeness is less in Luhansk, Zaporizhzhya and Dnipropetrovsk (0,5) regions. The least coefficient is typical for Kharkiv (0,4) and Kirovohrad (0,3) regions. This divergence caused by subject reasons requires reconsideration some methodical approaches, in particular in rare part of the Statute on the Econet Formation of Ukraine. First of all, it is related to fixation of the priority principle of representativeness in the econet components of all or maximally full rare phytodiversity of the administrative region or physicogeographical territory. The task of fullness problem of population representativeness of rare species is also very important and should be decided.
Keywords: econet, sozophytes, protection, steppe.